Diplomasi Publik dan Soft Power: Sama atau Berbeda? - Trisni, Sofia; Putri, Ardila (Andalas Institute of International Studies UNAND, 2023)
Public diplomacy has been a long-standing practice that continues to this day. Both developed and developing countries aim to design public diplomacy programs that are well-received by their target audience. Public diplomacy is closely linked to the concept of soft power, which became popular after Joseph Nye coined the term in the 1990s. Countries implement public diplomacy because they believe it can enhance their soft power. In Indonesia, the relationship between public diplomacy and soft power has been widely discussed in academic articles. However, there still needs to be a consensus on whether the two concepts are the same or different. This article aims to clarify their relationship using a literature review of articles written by leading scholars in the field. Based on the review, it can be concluded that public diplomacy and soft power are different but interconnected. Public diplomacy is often implemented to promote or generate soft power.